2022
DOI: 10.3390/buildings12010043
|View full text |Cite
|
Sign up to set email alerts
|

Specific Skill Requirements within Prefabricated Residential Construction: Stakeholders’ Perspectives

Abstract: Skill availability is an important component in the uptake of prefabrication and plays a crucial role in housing supply. However, the challenge is that the demand for housing has outgrown the availability of specifically trained workers. This challenge is not unique to New Zealand; many developed countries worldwide are facing similar issues. Therefore, the purpose of this study is to determine relevant skills in the prefabricated residential construction sector in New Zealand (NZ) and suggest improvement meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Articles without authors related to prefabricated/off-site building construction were removed. They were constructed under a controlled nature, procuring bulk of materials, using different technology and special skills required [36]. Therefore, acquisition costs differed from the inflation's effect on acquisition costs, which differs from on-site construction.…”
Section: Methodsmentioning
confidence: 99%
“…Articles without authors related to prefabricated/off-site building construction were removed. They were constructed under a controlled nature, procuring bulk of materials, using different technology and special skills required [36]. Therefore, acquisition costs differed from the inflation's effect on acquisition costs, which differs from on-site construction.…”
Section: Methodsmentioning
confidence: 99%
“…Housing design is for living and providing comfort, and it is a basic human need [17]. Housing is a basic and sensitive sector in economic and social development planning, but still, a large number of the world's population lacks an appropriate house [18].…”
Section: Housing Architecturementioning
confidence: 99%
“…The shape of housing can be changed by climatic conditions, structural technology, and available materials [37]. The space's identity depends on the physical environment and its quality [17]. The interior spaces consist of enclosed and private spaces, and the external spaces, including open and public spaces, are the two main housing components [38].…”
Section: Housing Architecturementioning
confidence: 99%
“…At the same time, developers, as prominent participants in developing prefabricated buildings, have also received much attention. Based on online research, Rotimi found that the obstacles to developing prefabricated buildings are closely related to the professional skills shortage of relevant management, design, and residential construction practitioners [ 35 ]. Lee compared and analyzed the implementation conditions of modular buildings based on actual development cases and concluded that the construction cost was high [ 36 ].…”
Section: Literature Reviewmentioning
confidence: 99%